PELATIHAN PEMBUATAN KARTU IDENTITAS(ID CARD) MENGGUNAKAN APLIKASI CORELDRAW BAGI SISWA SMK NU TENGGARANG - Zaehol Fatah; Shinta Nuriyah Lailatul Iqrimah (Jurnal Padamu Negeri, 2026)
The swift progression of digital technology demands that vocational high school students acquire graphic design competencies that align with current industry standards. One valuable skill to foster is the creation of identification cards (ID cards) through the use of design applications. This study seeks to describe the implementation of ID card design training using CorelDRAW and to assess the progress in students' skills at SMK NU Tenggarang following their engagement in the program. A descriptive quantitative design served as the methodological framework, with data gathered through observation, document analysis, questionnaires, and assessment of students' design outputs. The training series covered fundamental concepts of graphic design, exploration of CorelDRAW features, hands-on practice in ID card creation, and final project evaluation. The results revealed that students demonstrated considerable improvement in both operating CorelDRAW and generating visually appealing and effectively communicative ID card designs. Furthermore, participants showed high program was found to be successful in advancing students' graphic design capabilities and digital literacy within the vocational education context.levels of motivation and offered positive responses throughout the training activities. In conclusion, the In conclusion, the training program successfully improved students' graphic design skills and digital literacy in the vocational education environment. The majority of participants achieved competency in creating professional ID card designs using CorelDRAW.